PEMANFAATAN AUGMENTED REALITY SEBAGAI PENGENALAN PLANET – PLANET TATA SURYA PADA SEKOLAH MA MUHAMMADIYAH PEKANBARU - vitriani; Silva , Silva Futri Ananda.H; Hafiz, Hafiz Attamimi; Malik, Malik Fajar (Unit Pelaksana Praktik Kependidikan Terpadu Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Riau, 2025)
This research aims to develop innovative, interactive learning media based on advanced Augmented Reality (AR) technology to help students understand the concept of the solar system in depth and comprehensively. Using the ADDIE research method, this application was designed with Unity 3D and Vuforia, utilizing flash cards as markers to display 3D objects realistically, dynamically and in detail. This application has proven effective in increasing the attractiveness of learning, maximizing students' understanding of complex material, and providing a more interesting, deep, immersive and interactive learning experience. With the Android platform, this application is a modern learning innovation that is easy to access, flexible, relevant to the needs of the digital era, and has great potential to be applied more widely in various subjects and other concepts, thereby supporting the improvement of the overall quality of education.